ALASAN DAN IZIN POLIGAMI (SEBUAH PENDEKATAN TEORITIS HUKUM KELUARGA ISLAM) - Arif Hariyanto; Ach. Azaim Ibrahimy (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
Marriage is one of the most important basic principles of life in a perfect society or association, marriage is not only a very noble way to organize household life and offspring, but can also be seen as a way to the door of introduction between one people and another. Marriage is a necessity of life for all people from ancient times to the present. Because marriage is an actual problem to be discussed inside and outside the law. One of them is the problem of polygamous marriage which since the time of the Prophet until now is still a trending topic in the sense that it is still hotly discussed, especially for women who are important objects in it and there are several conditions that must be met. Where without these conditions a husband cannot practice polygamy. One of them must be able to be fair to his wives. In addition, fairness is also the main requirement that must be met in polygamy, both alternative and cumulative.